Mapping of herbs farming as the theme of Catur Tourism Village, Kintamani, Bangli, Bali, Indonesia - I Gusti Bagus Rai Utama; Ni Made Diana Erfiani; Dermawan Wuruwu; Putu Chris Susanto; I Putu Darmawijaya; Christimulia Purnama Trimurti; Ni Putu Dyah Krismawintari (International Journal of Applied Sciences in Tourism and Events, 2022)
The purpose of this research is to formulate a mapping model on the potential of an herbal-themed tourism village based on a case study in Catur Village, Kintamani, Bangli, Bali. The methodology of the research is a qualitative descriptive study by conducting a field survey, namely collecting data by providing closed questions that ask the perceptions of stakeholders managing tourism villages in Bangli Regency, community leaders in Catur Village, small business owners in Catur Village, and the Village Heads. The research results are processed using descriptive statistical analysis techniques by visually describing a set of data, which can be done in two parts, namely numerical descriptions, narrative texts, graphics, and in-depth explanations. Results of research of the descriptive analysis using tourism village mapping indicators posted Catur Tourism Village as a fairly decent village (2.52) to be further developed as a tourist village. This tourist village is mapped into four potentials, namely: nature tourism, cultural or religious tourism, herbal tourism, and agri-horticultural. Conclusion of the results of research based on the analysis of tourism potential, it can be said that Catur Village has fulfilled four aspects (4A) in offering tourism product of four main attractions, namely natural beauty, agriculture, culture or religion, and herbs. In terms of accessibility, road access to Catur is very adequate. In terms of amenities, facilities such as homestays, food and beverage providers, banks, health services, and others are quite available at Catur. As for ancillary, the institutions in Catur have led to full support for the development of the tourist village.